Effect of Project-Based Teaching Strategies on Cognitive and Social Skills Development of Primary School Pupils in Ogun East Senatorial District - Ogunyemi, F. Taiwo; Oladele, Michael T.; Gbadegesin, Motunrayo. A; Zakariyyah, Fatimah; Sokoya, Taiwo Omobolanle (Kashere Journal of Education, 2026)
The study investigated the effect of project-based teaching strategy on cognitive and social skills development of primary school pupils in Ogun East Senatorial District of Ogun State. The main objective of this study was to investigate the main effect of project-based teaching strategies, attitude, and gender on cognitive and social skill development of primary school pupils. Quasi-experimental research design was adopted for the study. The population was primary six (6) pupils. A sample size of 154 pupils selected from four (4) public primary school took part in the study. Enumeration method was used to select Ogun State senatorial district. Purposive sampling was used to select a local government area. Two schools were assigned to an experimental and one control group using convenience sampling. Crombach Alpha was used to validate instrument on cognitive and social skills development at index of 0.821. Moderating variables of Gender and attitude of learners were examined on the outcome variable. Data were analyzed, using inferential statistics of Analysis of Covariance (ANCOVA) were used to answer research questions and test the hypotheses at 0.05 level of significance. The results of the study indicate that the Experimental Group (project-based teaching strategies) performed better (mean score = 99.72) than the Control group (conventional strategy) (with mean score 92.9) confirming that treatment had differential effects on Cognitive Skills development among primary school pupils. Similarly, there is a significant main effect of treatment (project-based strategy) on Social Skills Development among Primary School pupils (F (2, 141) = 6.090, P < .05 = 0.003). It was concluded from findings of the study that project-based teaching strategy had significant effect on cognitive and social skills development of primary school pupils. Based on the finding of the study, a step-by-step user-friendly teaching guides on project-based strategies should be designed by teachers to enhance the readiness and interest of primary school pupils towards learning.